Peran Kompetensi Komunikasi Bisnis dalam Kesuksesan Wirausaha Mahasiswa STIE Ganesha - Nurhayati Nurhayati; Budi Prajogo; Farhat Abas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the relationship between business communication competencies obtained during education at STIE Ganesha and success in developing businesses or startups by students. With a focus on twenty students who are active entrepreneurs, this research uses a qualitative approach to collect and analyze data. Through in-depth interviews and content analysis of business communications carried out, this research identifies how communication skills such as negotiation, presentation, and interpersonal communication contribute to their entrepreneurial success. The research results show that students with higher business communication competencies tend to experience greater success in their entrepreneurial activities. These findings imply the importance of integrating effective business communication training in higher education curricula, especially for students interested in entrepreneurship. It is hoped that further implications of this research will provide insight to educational institutions to develop communication training modules that are more effective and relevant to the needs of the job market.